Insular adaptations in the appendicular skeleton of Sicilian and Maltese dwarf elephants - Scarborough, Matthew Edward (Department of Biological Sciences, 2021)
This thesis investigates the evolution of Pleistocene insular proboscideans from the centralwestern Mediterranean (Palaeoloxodon species from Sicily, Malta, Favignana) and a mammoth (Mammuthus lamarmorai) from Sardinia, with a particular emphasis on the anatomy of the limbs. Differences in the morphology of the limbs are examined across a tenfold reduction in mass (from 3,5m-tall P. antiquus from Germany to 1,2 m-tall P. ex gr. P. falconeri from Spinagallo Cave, Sicily), revealing insights into significant morphological changes in the long and foot-bones, particularly appendicular changes evident in SiculoMaltese P. ex gr. P. falconeri. Notable morphological differences between P. antiquus and its insular descendent P. ex gr. P. falconeri include the functional morphology of the ankle-joint (especially the calcaneus' articular facet for the tibia). Furthermore, morphological similarities found between the femur of young continental elephants (P. antiquus and L. africana) and adult insular dwarfs (P. ex gr. P. falconeri and its probable ancestor Palaeoloxodon sp. from Lparello Fissure, Sicily) suggest evidence of paedomorphism in the limbs. Similarly, comparisons of the ontogenetic allometry of the tibia in L. africana and P. ex gr. P. falconceri include changes which are also consistent with paedomorphism, although other factors could not be ruled out. In the humerus large differences are evident in the morphology of the deltoid tubercule between co-generic insular Palaeoloxodon species, suggesting interspecific differences in the musculo-skeletal system. Furthermore, on the basis of dimensions, morphology and stratigraphy, the large Palaeoloxodon sp. remains from Luparello Fissure, north-western Sicily are suggested to belong to the ancestral chronospecies of P. ex gr. P. falconeri from Sicily, which may have subsequently colonized Malta during the reduced sea-levels of a Middle Pleistocene glacial lowstand (following a corridor with reduced distances between the two islands). Additionally, morphological differences in the calcanei of elephants from Luparello Fissure, Sicily, and Benghisa Gap, Malta may be the result of allopatric speciation between similar-sized elephants during the Middle Pleistocene, or alternatively relate to ecomorphology. These findings suggest that the morphology of the calcaneus may be more informative than hitherto recognised for resolving systematics and taxonomy among the Elephantini. Furthermore, although the absolute chronology of SiculoMaltese elephants remains poorly constrained, preliminary U-Th dating at Alcamo Quarry, western Sicily suggests a tentative early Middle Pleistocene age for Palaeoloxodon sp.